2016
DOI: 10.1002/2015jd024039
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric temperature changes during the satellite era

Abstract: Satellite‐based layer average stratospheric temperature (T) climate data records (CDRs) now span more than three decades and so can elucidate climate variability associated with processes on multiple time scales. We intercompare and analyze available published T CDRs covering at least two decades, with a focus on Stratospheric Sounding Unit (SSU) and Microwave Sounding Unit (MSU) CDRs. Recent research has reduced but not eliminated discrepancies between SSU CDRs developed by NOAA and the UK Meteorological Offi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 71 publications
(127 reference statements)
7
62
0
Order By: Relevance
“…The satellite weighting functions for these three channels can be found in Fujiwara et al (2017, their Fig. 7) and Seidel et al (2016, their Fig. 1 (Zhao et al, 2016).…”
Section: Atmospheric Layer Temperature Anomaliesmentioning
confidence: 99%
See 1 more Smart Citation
“…The satellite weighting functions for these three channels can be found in Fujiwara et al (2017, their Fig. 7) and Seidel et al (2016, their Fig. 1 (Zhao et al, 2016).…”
Section: Atmospheric Layer Temperature Anomaliesmentioning
confidence: 99%
“…Other studies use these temperature data records to monitor changes in the Brewer-Dobson circulation (Young et al, 2011(Young et al, , 2012. Randel et al (2016) compared global and latitudinal trends from SSU with Aura MLS and SABER temperatures. Simmons et al (2014) discuss the impacts of the MSU, SSU, AMSU-A, HIRS, and AIRS channels assimilated in the ERA-I.…”
Section: Atmospheric Layer Temperature Anomaliesmentioning
confidence: 99%
“…Above all, we believe that the ENSO signal may also modulate the amplitude of the TO, mainly in the lower stratosphere. Several studies have revealed that the El Nino-Southern Oscillation (ENSO) can influence the tropical stratospheric temperature [48][49][50]. The ENSO variations can be characterized by the Multivariate ENSO Index (MEI) [51].…”
Section: The Long-term Variations Observed By Fpimentioning
confidence: 99%
“…The robustness of the temperature trends in the lower stratosphere derived from radiosondes (since 1958) and from satellites (since 1979) suffers from instrumental uncertainties such as sensor changes, drifts, etc., implying large uncertainties in the trend estimates (Simmons et al, 2014). In recent years, several studies assessed the uncertainty of temperature trends in the lower stratosphere and the impact on changing trends of radiatively active constituents (such as ozone) or atmospheric dynamics (e.g., Fueglistaler et al, 2014;Seidel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Since 1995, the cooling turned into a neutral trend with a larger increase (not significant) over the Antarctic region than over the tropics (Randel et al, 2009;Blunden and Arndt, 2014;Seidel et al, 2016). The robustness of the temperature trends in the lower stratosphere derived from radiosondes (since 1958) and from satellites (since 1979) suffers from instrumental uncertainties such as sensor changes, drifts, etc., implying large uncertainties in the trend estimates (Simmons et al, 2014).…”
Section: Introductionmentioning
confidence: 99%